2007
DOI: 10.1002/cyto.a.20334
|View full text |Cite
|
Sign up to set email alerts
|

Fully automated segmentation and morphometrical analysis of muscle fiber images

Abstract: Background: Measurement of muscle fiber size and determination of size distribution is important in the assessment of neuromuscular disease. Fiber size estimation by simple inspection is inaccurate and subjective. Manual segmentation and measurement are time-consuming and tedious. We therefore propose an automated image analysis method for objective, reproducible, and time-saving measurement of muscle fibers in routinely hematoxylineosin stained cryostat sections. Methods: The proposed segmentation technique m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…The presence of sub-G1 peaks on DNA content histograms is generally accepted to represent apoptotic cells (20). As cell cycle analysis demonstrated that combined pitavastatin-DTIC treatment resulted in sub-G1 peaks ( Fig.…”
Section: Combined Pitavastatin and Dtic Treatment Induces G1 Cell Cycmentioning
confidence: 99%
“…The presence of sub-G1 peaks on DNA content histograms is generally accepted to represent apoptotic cells (20). As cell cycle analysis demonstrated that combined pitavastatin-DTIC treatment resulted in sub-G1 peaks ( Fig.…”
Section: Combined Pitavastatin and Dtic Treatment Induces G1 Cell Cycmentioning
confidence: 99%
“…To the best of our knowledge, this is the largest and most comprehensive dataset of images analyzed in a neuromuscular study. Previous reports have been published of attempts to facilitate the automated extraction of geometric characteristics from muscle biopsies [11][12][13][14][15][16]. These studies rely on the development of segmentation methods using a very small number of samples to only extract morphometric information.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was surprising that the 'degree of neighbors' was more important than features related to the shape of the fibers. Interestingly, none of the previous characteristics (15,18,19) were selected when control and NA (12,20,21,22) were compared. The three network characteristics selected are related to the organization of the fiber types and were able to capture the characteristic fibertype grouping due to secondary reinnervation events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are several publications on automatic detection and classification of nuclei and FISH analysis on fluorescent images (35)(36)(37) and complex automated segmentation methods for membrane and muscle fiber for example (31,38).…”
Section: Quantitative Imagingmentioning
confidence: 99%